Obesity Is Not a Predictor of Complications in Upper Extremity Surgery. (March 2019) - Golan, Elan J.; De Tolla, Jadie; Culbertson-Scott, Maya Deza; Krochak, Ryan; Choueka, Jack
Background: Obesity is an often-cited cause of surgical morbidity. As a result, many institutions have required screening prior to "clearing" obese individuals for surgery. However, it remains unclear whether such testing is warranted for obese patients prior to upper extremity procedures. This study reviews surgical outcomes to determine if obesity does predict operative morbidity following upper extremity surgery.Methods : The National Surgical Quality Improvement Program was queried for 18 Current Procedural Terminology codes, representing upper extremity fracture and arthroplasty procedures. Patients' body mass index (BMI) and medical histories were examined as predictors for postoperative complications. Both individual and combined incidences of complications were compared between patients stratified as normal-weight (BMI < 30); obese (BMI 30-40); and morbidly obese (BMI> 40).Results : A total of 8, 477 patients were identified over the 5-year study period; 5, 303 had a BMI <30, 2, 565 a BMI of 30 to 40 and 585 a BMI >40. With the exception of postoperative blood transfusions, there were no significant increases in the incidence rates of any complication event as a function of BMI class. The overall incidence of complications was 2.70 % for BMI <30; 2.74 % for BMI 30 to 40; and 1.54 % for BMI >40.Conclusions : Obesity is not a reliable predictor of complications following upper extremity surgery. Thus, requiring preoperative screening for obese patients may constitute an unnecessary burden on medical resources. Further study is needed to identify specific demographics that might serve as more accurate predictors of poor outcomes in obese patients undergoing surgery of the upper extremity.